Study on Kitchen Waste Composting Using Microbial Cultures and Biochar - Budthapa, Kabita; Lawati, Kedipananda; Shrestha, Shova; Shrestha, Kanti (Journal of Sustainability and Environmental Management, 2025)
Kitchen waste has long contributed significantly to environmental pollution. The experiment titled “Study on kitchen waste composting using microbial cultures and biochar”, conducted at Nepal Academy of Science and Technology, Lalitpur, was meant to find the possible ways to shorten the composting period. Seven treatments were arranged in a completely randomized design (CRD): T1 (Control), T2 (EM-1), T3 (Prarhamva Decomposer), T4 (Biofertilizer KM), T5 (Biochar 400 g + Biofertilizer KM), T6 (Biochar 800 g + Biofertilizer KM), and T7 (Biochar 200 g). The decomposition period ranged from 14 to 33 days across treatments. The key finding was a significant reduction in composting duration, with T6 (800 g Biochar + Biofertilizer KM) achieving the fastest decomposition in just 14 days (p < 0.05), effectively reducing the composting time by more than half compared with the control (T1) and EM-1 (T2), both of which required 33 days. Chemical analysis revealed that T2 (EM-1) produced the highest nitrogen (0.55%) and organic matter (30.09%) content, whereas the highest phosphorus content (2.17%) was found in T3 (Prarhamva Decomposer), and the highest potassium (4.77%) was recorded in T5 (Biochar 400 g + Biofertilizer KM). Although temperature fluctuations were observed during different phases of decomposition, the integration of biochar and Biofertilizer KM consistently enhanced the composting process. These results demonstrate that biochar enrichment can significantly shorten the composting cycle, offering a robust platform for sustainable solid waste management.